PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR BEAT PADA DEALER CV.ZAM-ZAM HONDA MOTOR LUBUK JAMBI - Atika Safitri; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRAK The purpose of this study was to determine the effect of product quality and service quality on purchasing decisions of Beat motorbikes at CV.Zam-Zam Honda Motor Lubuk Jambi Dealers. This research uses quantitative analysis method. The sample in this study were consumers who bought Beat motorbikes at CV.Zam-Zam Honda Motor Lubuk Jambi dealers as many as 99 respondents. With data sources from primary data and secondary data. The analysis tool used in this research is SPSS version 23. The results of the research that has been done show that product quality has a significant effect on purchasing decisions for Beat motorbikes at CV. Zam-Zam Honda Motor Lubuk Jambi Dealers, service quality has a significant effect on the decision to purchase Beat motorbikes at CV. Zam-Zam Honda Motor Lubuk Jambi Dealers, and product quality and service quality have a significant effect on the decision to purchase Beat motorbikes at CV. Zam-Zam Honda Motor Lubuk Jambi Dealers. Keywords: Product Quality, Service Quality, and Purchase Decision